Enhancing energy extraction from water microdroplets through synergistic electrokinetic and galvanic effects - Li, Haitao (2024)
Water-evaporation generators fabricated from carbon black are an emerging approach for autonomous power generation, but they generally suffer from low power density. Here, our work introduces an efficient water-evaporation generator with high output power density and subsequently demonstrates its application for fabricating a self-powered device to power electronic devices. Our WEG design comprises two important components: (1) cotton fabric loaded with Ketjen carbon black to form a Ketjen carbon black/cotton fabric composite as the electroactive layer and (2) iron metal electrodes to impart galvanic effects for enhanced power generation. When using deionized water as an energy feedstock (25 °C; 50% RH), the optimized WEG produces a high maximum open-circuit voltage of 640 mV, short-circuit current of 140 μA, and power density of 250 μW g−1. Notably, the use of concentrated saline (13.5 wt% NaCl) instead of deionized water drastically boosts electrical outputs to 1 V, 0.6 mA, and 1.75 mW g−1, respectively, amounting to a total output energy of 659.4 kJ m−2 L−1. The superior performance of the WEG is attributed to the enhanced electrokinetic effects of Ketjen carbon black and effective integration with the galvanic effects from the iron electrode, thereby achieving remarkable electrical outputs that surpass those of existing generator designs by two orders of magnitude. These electrical outputs can be efficiently utilized to power personal electronic devices. More importantly, our article further showcases a combination of a typical generator with a water sponge to create an integrated, multifunctional smart bracelet for the real-time monitoring of human pulse information using an aqueous solution as a viable energy feedstock. Our work opens up vast opportunities for the production of green energy and the development of diverse applications in the field of wearable technology.